Efektifitas Penggunaan Teknologi Pertanian Terhadap Perubahan Sosial Masyarakatdesa Tawiri Kecamata Teluk Ambon - Melamas, Rina; Siwalette, J. D.; Pattiselano, August E. (Al Makki Publisher, 2025)
The effectiveness of the use of agricultural technology on social change in the Tawiri village community, Teluk Ambon sub-district, This study aims to examine the effectiveness of the use of agricultural technology on social change in the community in Tawiri Village, Teluk Ambon District. With the background that agriculture is the main sector of the economy in the area, this study identifies how the adoption of modern agricultural technology can improve farmers' welfare and affect their work routines. The research method used is qualitative, with data collection through questionnaires, in-depth interviews, and field observations. The results of the study indicate that the use of agricultural technology, such as modern machinery and digital agricultural systems, contributes to increasing farmer productivity and income. However, these changes also bring social challenges, such as reduced social interaction between farmers and impacts on the workforce. This study provides important insights for the government and related institutions in formulating policies that support agricultural modernization without ignoring the social values ​​of the community.